Consumers’ preferences for animal-source foods and retail outlets: The case of Tanzania - Baker, Derek; Mtimet, Nadhem; Pica-Ciamarra, U.; Nsiima, L. (2016)
Growth in population and income, as well as urbanisation, are contributing to the growing consumption of high-value foods in developing countries. However, public and private investments targeting high-value agricultural markets are constrained by limited information on the quality dimensions of the market, the nature of traditional retail formats, and consumer segmentation. This paper presents a simple and appropriate methodology to provide such information, and applies it in Tanzania to animal-sourced foods. It features a rapid survey, which is then aligned with nationally representative survey data. The results show that Tanzanian consumers demand, and are anticipated to continue demanding, relatively good-quality animal products but in rather low-valued product forms. Consumer segments are differentiated by level of wealth and by choice of retail format and retail product form, rather than by quality per se.